The Influence of Open Unemployment Rates, Inflation and Minimum Wages on Income Inequality in The North Sumatra Region - Nurdini; Yusrizal; Aqwa Naser Daulay (Jurnal Manajemen Bisnis, 2024)
Income inequality is the existence of differences in income in a society, giving rise to real income inequality in society. As a result, the rich get richer and the poor get poorer. In fact, when it comes to income inequality, the more flexible wages are, the greater the impact on employment. However, inflexible wages, which are said to be an inability to respond to changing market conditions, lead to ever-increasing poverty and inequality. This research aims to determine the correlation between the influence of open poverty levels, inflation and minimum wages on income inequality in North Sumatra. The Central Statistics Agency (BPS) noted that the level of expenditure disparity between residents in North Sumatra has widened since September 2023. The Gini ratio, which measures this inequality, is recorded as high. BPS Based on North Sumatra data, this large deviation was caused by the increase in fuel prices at the beginning of September last year. The research method used is Multiple Linear Regression which is processed using eviews 10 software. The approach used in this research uses a quantitative approach with associative analysis, with a population from the North Sumatra BPS report for 2014-2023. The results show that the open unemployment rate and minimum wage have an effect on income inequality. Therefore, the solution offered is a policy of establishing equal distribution of employment income by opening job vacancies and training as well as equal distribution of salary income which is applied evenly in various regions so as to reduce income inequality in North Sumatra